PLANT MEDIATED SYNTHESIS OF SILVER NANOPARTICLES WITH DIVERSE APPLICATIONS - KANCHANA, R.; ZANTYE, PRANJITA (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Green synthesis of multifunctional silver nanoparticles (SNP) using leaf extracts of Simarauba glauca and Artocarpus altilis, a good alternative to the electrochemical methods were exploited in this study for potential use as biomedical agent in medical field. Methods: Synthesis of silver nanoparticles using leaf extracts of Simarauba glauca and Artocarpus altilis was carried out. The SNPs were characterized by UV-visible spectrophotometry, Scanning electron microscopy (SEM) and Energy Dispersion spectral analysis (EDS) and evaluated for their multifunctionality. Results: The SNP were synthesised from the leaf extracts of Simarauba glauca and Artocarpus altilis using silver nitrate with the reaction time of two min and 10 min respectively. UV-visible absorption scan revealed a characteristic peak at 420nm indicative of the surface plasmon resonance for SNP. The synthesized silver nanoparticles were of size ranges from 33-50nm and 37.9 nm synthesised from the leaf extracts of Simarauba glauca and Artocarpus altilis respectively. Further the synthesized silver nanoparticles have shown excellent antibacterial activity against test pathogens, applicability in sewage water treatment and biofilm degradation and having perfect haemcompatibility. Conclusion: The biologically synthesized silver nanoparticles with these functionalities has transformed it to a multifunctional biomedical agent for potential use in medical field.